INOVASI COOKIES VEGETARIAN - Rachmat Astiana; Adhisty Zahrani Adrianto (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2023)
Recently, the trend of vegetarian has begun to be widely recognized by various groups in Indonesia. Not only is it recognized, but some people have started to adopt a vegetarian due to certain reasons. Therefore, many businesses in Indonesia are looking for opportunities from this trend, such as making vegetarian pastry products. Not only in Indonesia, there are also many food companies abroad that sell vegetarian products. Unfortunately, some of the ingredients used in making vegan cookies are a little difficult to find and the price is not cheap in Indonesia, based on the results of field surveys, most traditional markets and modern markets in Indonesia sell very few vegetarian substitutes. Therefore, the author feels the need to conduct a study to make innovative vegetarian cookies that use agar-agar, aquafaba and margarine as vegetarian substitutes. This study aims to determine the effect of taste, texture, color, aroma, on the innovation of vegetarian cookies, and then determine consumer acceptance and also the right formulation on the innovation of vegetarian cookies. The method used in this research is the experimental method; the data collection techniques used by the author are observation, literature study, organoleptic test, interviews. Based on the results of the research on vegetarian cookies innovation, each cookie has its own advantages, uniqueness and weaknesses. Where the results of the innovation of vegetarian cookies that use agar-agar as egg white and margarine as a substitute for butter, are superior to the innovation of vegetarian cookies that use aquafaba as egg white and margarine as a substitute for butter based on the results of the panelists' assessment Keywords : Innovation, Vegan Cookies, Aquafaba